Hubungan Model Pembelajaran Permainan Susun Kata terhadap Keaktifan Belajar Siswa Kelas III SDN 3 Jepang - Marliana Putri Lestari; Aulia Tri Lestari; Fitmaya Intan Nazwa; Fina Fakhriyah; Erik Aditia Ismaya (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Student learning engagement plays a crucial role in character development, especially at the elementary school level. To foster a positive learning environment and encourage active participation, active learning approaches based on games are considered effective. This study aims to analyze the relationship between the active learning model using word-building games and the learning engagement of third-grade students at SDN 3 Jepang, Kudus Regency. The research was motivated by the low level of student participation, which is still dominated by conventional teaching methods. A correlational quantitative approach was used, with a population consisting of all 20 third-grade students, who were also taken as the sample through total sampling technique. Data were collected using a questionnaire to measure learning engagement and observation of the implementation of the word-building game model. The Shapiro-Wilk test was used for normality testing, and since one of the variables was not normally distributed, the data were analyzed using the Spearman correlation test. The results showed a correlation coefficient of r = -0.097 with a significance value of 0.686 (> 0.05), indicating no significant relationship between the word-building game model and student engagement. Other factors such as individual learning styles or classroom atmosphere may influence student engagement. Nonetheless, this model still holds potential and should be further developed to align with elementary students' characteristics.